Cyanide toxicity. Bibliography research of its effects in animals and man - Ramírez, Augusto V. (2010)
Cyanide, hydrogen cyanide and its salts are called cyanide. They exist in natural form and are obtained as salts in industry. At low doses they are lethal in minimum exposure time. The nervous system is its primary target organ. After ingestion, contact or inhalation, serious neurotoxic effects appear in humans and animals. Occupational exposure can produce headache, vertigo, vomiting, nausea, thyroid gland alterations, and dermatitis. At high doses and in short time, cyanide exposure can end in death. In very low amounts some cyanide compounds are indispensable for life. Cyanide is located in group D “not classifiable as human carcinogen”. In order to apply preventive measures when working with cyanides and in public health, it is necessary to acknowledge cyanide toxic effects on men and animals.